The cryptotephra record of the Marine Isotope Stage 12 to 10 interval (460-335 ka) at Tenaghi Philippon, Greece: exploring chronological markers for the Middle Pleistocene of the Mediterranean region - Vakhrameeva, Polina; Koutsodendris, Andreas; Wulf, Sabine; Fletcher, William J.; Appelt, Oona; Knipping, Maria; Gertisser, Ralf; Trieloff, Mario; Pross, Jörg (Quaternary science reviews, 2018)
Precise chronologies that allow direct correlation of paleoclimate archives are a prerequisite for deciphering the spatiotemporal characteristics of short-term climate variability. Such chronologies can be established through the analysis of tephra layers that are preserved in the respective sedimentary archives. Here we explore the yet untapped tephrochronological potential of the Eastern Mediterranean region for the Middle Pleistocene, specifically for the interval spanning Marine Isotope Stages (MIS) 12-10 (460-335 ka). High-resolution cryptotephra analysis was carried out on peat cores spanning the MIS 12-10 interval that have been recovered from the iconic climate archive of Tenaghi Philippon, NE Greece. Eighteen primary cryptotephras were identified, and major- and trace-element analyses of single glass shards from all cryptotephras were performed in order to correlate them with their eruptive sources. The results suggest origins from both Italian and Aegean Arc volcanoes. Specifically, one cryptotephra layer could be firmly correlated with the Cape Therma 1 eruption from Santorini, which makes it the first distal tephra finding for this eruptive event. While eight further cryptotephras could be tentatively correlated with their volcanic or even eruptive sources, the provenance of another nine cryptotephras as yet remains unknown. The relatively large number of cryptotephras that could not be assigned to specific volcanic sources and eruptive events reflects the still considerable knowledge gap regarding the geochronology and geochemistry of proximal tephra deposits from the Middle Pleistocene of the Central and Eastern Mediterranean regions. Due to the lack of well-dated Middle Pleistocene eruptions, we provide age estimates for all cryptotephra layers identified in the MIS 12-10 interval at Tenaghi Philippon based on high-resolution pollen data from the same cores. While eight of the identified cryptotephras were deposited within MIS 12 (∼438-427 ka), one cryptotephra was deposited at the onset of MIS 11 (∼419 ka), five cryptotephras during the younger part of MIS 11 (∼391-367 ka), and four cryptotephras during MIS 10 (∼359-336 ka). The high number of cryptotephras from multiple sources as recorded in the MIS 12-10 interval at Tenaghi Philippon highlights the key role of this archive for linking tephrostratigraphic lattices for the Middle Pleistocene of the Central and Eastern Mediterranean regions.
Available online 10 October 2018
Gesehen am 14.08.2019